Physical properties of medium density fiberboard produced with the addition of ZnO nanoparticles - da Silva, Ana Paula Santos [UNESP]; Ferreira, Bruno Santos [UNESP]; Favarim, Higor Rogério [UNESP]; Felippe Silva, Maria Fernanda [UNESP]; Felippe Silva, João Vítor [UNESP]; Azambuja, Maximiliano dos Anjos [UNESP]; Campos, Cristiane Inácio de [UNESP] (BioResources, 2019)
The use of wood-base panels in humid environments, in general, presents low durability due to contact with water. In order to increase durability and reduce the attack of fungi, studies had been developed using resin with zinc oxide (ZnO) nanoparticles. This work aimed to produce medium density fiberboard with urea-formaldehyde resin and melamine-formaldehyde adding 0.5% and 1.0% of ZnO nanoparticles for the physical properties evaluation. All treatments were classified as medium density according to ABNT NBR 15.316-2 (2015) with values ranging between 550 and 800 kg*m -3 . No differences were found between the two commercial adhesives used. The addition of 1.0% of nanoparticles resulted in lower density panels, higher moisture contents, and, after immersion in water for 24 hours, higher values of swelling in thickness. These results are explained by the lower compaction of the boards due to rapid cure of the adhesive using higher percentages of ZnO nanoparticles. The best treatment of the panels was with melamine-formaldehyde resin and 0.5% of nanoparticles.
Keywords: Fiberboard; Nanotechnology; Physical characteristics